2001
DOI: 10.1034/j.1399-3046.2001.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus‐related post‐transplant lymphoproliferative disease in solid organ transplant recipients, 1988–97: A Canadian multi‐centre experience

Abstract: The aim of this work was to obtain information on the magnitude of the problem, disease characteristics, and clinical practices relating to post-transplant lymphoproliferative disease (PTLD) in Canadian institutions. Adult and pediatric Canadian solid organ transplant groups were sent a questionnaire between July and October 1998. Analyzable data were obtained from 33 transplant groups. For the period 1988-97, 90 cases of PTLD were seen among 4283 solid organ transplant recipients. The incidence of PTLD varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 18 publications
0
57
1
Order By: Relevance
“…30,31,37 A previous study reported that the monomorphic type occurred in 31%, polymorphic type in 19%, and hyperplastic form of early lesions in 1% patients. 38 Because the highest PTLD incidence and mortality were seen in pediatric liver transplant recipients, timely diagnosis of this complication before appearance of clinical symptoms is important. 29 Preventing PTLD by monitoring EBV loads after transplant should be considered, especially in infants, young children, and other patients who are at high risk of developing EBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…30,31,37 A previous study reported that the monomorphic type occurred in 31%, polymorphic type in 19%, and hyperplastic form of early lesions in 1% patients. 38 Because the highest PTLD incidence and mortality were seen in pediatric liver transplant recipients, timely diagnosis of this complication before appearance of clinical symptoms is important. 29 Preventing PTLD by monitoring EBV loads after transplant should be considered, especially in infants, young children, and other patients who are at high risk of developing EBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In moderate forms, a reduction of the immunosuppression allows the recipient to control the lymphoproliferation and to eventually fully recover [4,7,8,9]. However, when PTLD evolve towards a B-cell lymphoma, chemotherapy in association with surgery and/or immunotherapy remains the only therapeutic option [5,9,10].…”
Section: Introductionmentioning
confidence: 97%
“…However, severe neoplastic forms do occur. In children a mortality of 32%-49% has been reported [1,5,6]. An early diagnosis is essential for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…98 With 10% clinically meaningful responses, this rate is much lower in studies analyzing only monomorphic PTLD. 97,99,100 If the PTLD completely resolves with RIS, no further treatment may be required. After HSCT, RIS seems to be less efficient compared with SOT.…”
Section: Rismentioning
confidence: 99%